Pair A:
![7x+11y,11y+7x](https://img.qammunity.org/2023/formulas/mathematics/college/1l1z0gf6xq9k1jic2235htyn13h98v53o3.png)
Remember that characteristic of the numbers is that, in general:
![a+b=b+a](https://img.qammunity.org/2023/formulas/mathematics/college/hsu1x18584pvvkbyu47y72cp747tlzkr7d.png)
For any numbers a and b, this is always true. So, in our case:
![\begin{cases}a=7x \\ b=11y\end{cases}\Rightarrow7x+11y=11y+7x](https://img.qammunity.org/2023/formulas/mathematics/college/8u967vuw9v1kiyer7e2kmsgtisdl0e2jz6.png)
So the pair A is equivalent
As for pair B:
We are going to it by contradiction: if we suppose that the two equations are the same (one is equal to the other) and we found a pair of numbers (x,y) that produce a contradiction, then the two equations cannot be equivalent. Let me show you:
Suppose pair B is equivalent, then:
![3x+3y=6xy](https://img.qammunity.org/2023/formulas/mathematics/college/gna0vllp24iyoglvxmwh4addwofb1duuh5.png)
Now, suppose that x=0 and y=1, then:
![3(0)+3(1)=6(0)(1)\Rightarrow3=0!!](https://img.qammunity.org/2023/formulas/mathematics/college/efhk0m99ixh0v2ixasnkrntj46ctnbslzg.png)
And of course, 3 is not equal to 0!
So, by supposing that the 2 equations are equivalent we reach a false implication, which means that the pair is NOT equivalent
As for pair C:
We can expand the expression 6(2x-y):
![6(2x-y)=6(2x)-6(y)=12x-6y](https://img.qammunity.org/2023/formulas/mathematics/college/ggw1n5pjk7ckd7iexakz3qixonrxjwm65j.png)
Which is exactly the first expression! So the pair is equivalent!